Handbook on public and private security - Blackstone, Erwin A.; Hakim, Simon; Meehan, Brian (Competitive Government: Public Private Partnerships, 2023)
1. An Overview of Private Security and Policing in the United States -- 2. Allocating Police and Security: Comparing Public and Private Processes and Consequences -- 3. Public Space Crime Prevention Partnerships: Reviewing the Evidence -- 4. Australian Public and Private Crime Prevention Partnerships in Cyberspace -- 5. Private Security Confounds Estimates of Public Police and Crime -- 6. Public-Private Security Partnerships. Can they meet the Growing Challenges of Law Enforcement?- 7. The COVID-19 Pandemic and its impact on Public-Private Partnership in Policing: Experiences from within the Belgian and Dutch Security Industry -- 8. Incorporating Non-State Security Actors into Public Security: Mexico’s Failed Experiment -- 9. The Substitutability and Complementarity of Private Security with Public Police: The Case of Violence Against Women and Girls in the Rail Network of the United Kingdom -- 10. Working with Private Policing to Enhance Public Policing: The Case of the United Kingdom -- 11. Private Law Enforcement in New York City -- 12. Private Security and Deterrence -- 13. How to Fight Crime by Improving Police Services: Evidence from the French Quarter Task Force -- 14. Public Security Enhances the Effectiveness of Private Security in Reducing Maritime Piracy Harm -- 15. What We’ve Learned: Lessons from the World’s Leading Security Companies on Partnerships and Privatization -- 16. Improving Public Safety through Law Enforcement and Private Security -- 17. The Importance of Public-Private Partnerships -- 18. New Realities and New Solutions in Public and Private Policing .